Penyesuaian perkawinan pada pelaku pernikahan dini: Adakah peranan kematangan emosi? - Anisa Khaerani; I Gusti Ayu Agung Noviekayati; Alifia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract Marital adjustment is a process of adaptation of husband and wife, where the husband and wife can prevent conflicts and resolve conflicts properly and there is a relationship of mutualism (mutual benefit) between husband and wife to give and receive (fulfill obligations and receive rights). To find out the relationship between emotional maturity with marriage adjustment in early age couples on Bawean Island. The subjects in this study were women who were engaged in early marriage whose marriage age span was more than 3 years on the island of Bawean, based on a predetermined population. The sampling technique used in this study is non-probability sampling, using incidental sampling. The results of the correlation test concluded that there was a significant positive correlation between the variables of emotional maturity and marital adjustment in 34 early-age couples in Bawean. This could mean that the higher the emotional maturity of an individual, the higher the marital adjustments made. Keywords: Emotional Maturity, Marriage Adjustment